Pengaruh Celebrity Endorsement Bintang Emon dan Social Media Marketing terhadap Purchase Intention Melalui Brand Trust pada Smartphone Samsung: - Pramestyi Utami; IBN Udayana; Nonik Kusuma Ningrum (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Industry 4.0 originates from the idea of ​​the Industrial Revolution The four industrial revolutions occurred four times. The industrial revolution 4.0 has changed many things, for example the way we communicate. Nowadays we can communicate easily through smartphones. Based on the discussion above, the purpose of this research is to examine the effect of purchase intention, celebrity endorsement, social media marketing and brand trust as intervening variables. This research is quantitative in nature by taking 100 samples of consumers of Samsung smartphone products in the city of Yogyakarta. Sampling was carried out using a non-probability method and using a sampling technique, namely purposive sampling. Data collection was carried out online by sending questionnaire links to respondents. Data were analyzed using the IBM SPSS application. The results of this study indicate that the celebrity endorsement variable (X1) has a significant positive effect on brand trust (Z) with a value of 0.000. Then the social media marketing variable (X2) has a significant positive effect on brand trust (Z) with a value of 0.000. Brand trust variable (Z) has a significant positive effect on purchase intention (Y) with a value of 0.000. Furthermore, the celebrity endorsement variable (X1) has a significant positive effect on purchase intention (Y) with a value of 0.020. And the social media marketing variable (X2) has a significant positive effect on purchase intention (Y) with a value of 0.042. In addition, the results of the study also show that brand trust is able to act as an intervening variable in the influence of celebrity endorsements and social media marketing on consumer purchase intentions for Samsung smartphone products in the city of Yogyakarta. Keywords: Celebrity Endorsements; Social Media Marketing; Brand Trusts; Purchase Intentions